The Role of Color in User Experience: A Systematic Literature Study of User Preferences for Dark and Light Mode - M. Rifqi Atsani; Iif Alfiatul Mukaromah; M. Haikal Citra Anugerah (Transactions on Informatics and Data Science, 2025)
The increasing use of dark mode and light mode in user interfaces has prompted many studies to determine their effects on user experience. Findings in the literature show that research is still fragmented and does not provide a comprehensive understanding of the cognitive, emotional, and behavioral aspects of preferences for user interface themes. This study analyzed 25 selected scientific articles from 2020 to 2025. The identification topics were related to user preferences, performance, accessibility, and satisfaction with interface modes. The qualitative thematic analysis approach found 6 main themes, namely Readability and Accessibility, Cognitive and Emotional Responses, Usage Behavior and Preferences, Task Performance and Efficiency, Health and Environmental Impacts, and Interface Design and Satisfaction. The results showed that light mode was better in terms of readability and tasks that require high lighting, dark mode provides better visual comfort than light mode and reduces eye fatigue in low light conditions. User preferences were influenced by several things such as age, device type, environment, and emotional needs. This research emphasizes the development of an adaptive system that allows users to switch between dark and light modes according to their respective conditions is important. This research contributes to the field of Human Computer Interaction (HCI) by demonstrating an understanding of interface theme design as well as future research directions.